Absorption P of Soybean Plants ( Glycine max L.(Merr)) in Cambisol Soil After Lime and Phosphate Fertilizer Application - Charles Silahooy (PT Inovasi Pratama Internasional, 2023)
Lime and fertilization are the right way to increase nutrients to increase P uptake of soybean plants ( Glycine max L. ( Merr)) on cambisol soil. This is done by paying attention to the dose, time, and method of calcification and fertilization. This study aims to obtain information about the P uptake of soybean plants ( Glycine max L. ( Merr)) on cambisol soil after lime and phosphate fertilizer application, which was carried out in Poka Village, Teluk Ambon Baguala District, Ambon City. This research took place from September 2022 to February 2023. Soil and plant analysis was carried out at the Soil Laboratory, Faculty of Agriculture, University of Pattimura. The experimental design used in this study was a factorial complete randomized design (CRD) with three replications, where the parameter studied was the P uptake of soybean plants. The results showed that the optimal combination of lime and phosphate fertilizer doses on cambisol soil could increase the P uptake of soybean plants.